Acquired Von Willebrand syndrome in patients on long-term support with HeartMate II. (7th December 2016) - Heilmann, Claudia; Trummer, Georg; Beyersdorf, Friedhelm; Brehm, Kerstin; Berchtold-Herz, Michael; Schelling, Johannes; Geisen, Ulrich; Zieger, Barbara
Abstract: OBJECTIVES: Impaired binding of Von Willebrand factor (VWF) to platelets and to collagen due to acquired Von Willebrand syndrome (AVWS) is associated with support from a ventricular assist device (VAD) and can contribute to bleeding tendencies in patients with VADs. The onset of AVWS has been shown to occur immediately after VAD implantation. Our aim was to determine long-term data on AVWS in VAD patients. METHODS: We analysed 278 data sets of 74 patients on HeartMate II (HMII) support for 3–80 months after implantation (11.2 ± 12.1, median 6.3 months.). Ristocetin cofactor activity (VWF:RCo), collagen binding capacity (VWF:CB), VWF antigen (VWF:Ag) and the ratios of VWF:RCo/VWF:Ag and VWF:CB/VWF:Ag were determined. Further, the presence of high molecular weight (HMW) multimers of VWF was investigated. RESULTS: Abnormally low values of VWF:RCo/VWF:Ag and VWF:CB/VWF:Ag were found in 69% and 97% of blood samples, respectively. Only ten of 181 multimer analyses showed a normal pattern, and HMW multimers were present in both specimens in only one of the 74 patients. No significant changes in these parameters were observed over time. The VWF:CB/VWF:Ag ratio correlated with the multimer patterns, whereas the VWF:RCo/VWF:Ag ratio seemed to be less sensitive for AVWS. CONCLUSION: Our data indicate that AVWS is a typical phenomenon in patients with VAD support and that there are no time-dependent changes in these parameters apparent in most patients on long-term support with HMII.